Effectiveness of integrative medicine program for dementia prevention on cognitive function and depression of elderly in a public health center - Hae In Ahn; Min Kyung Hyun (Integrative Medicine Research)
Background: This study investigated the effectiveness of an integrative medicine program (IMP) for dementia prevention on cognitive function, depression and quality of life (QOL) of elderly in a public health center. Methods: This study employed a before-after study design to assess effectiveness of the IMP for dementia prevention for community dwelling elderly over 60 without diagnosis of dementia. Cognitive function was measured using the Mini Mental State Examination for Dementia screening (MMSE-DS), digit span test (DST) and trail making test (TMT). The Geriatric Depression Scale Short Form- Korean version (GDSSF-K) and EQ-5D were used to evaluate depression and health-related quality of life. The IMP composed of acupuncture, moxibustion, physical activities, meditation, laughter therapy and music therapy was held once a week over 8 weeks. A paired t-test was used to compare the pre and post-test results. Results: After screening 93 people, a total of 48 were included in the analysis. Evaluation of the cognitive function revealed that TMT-A (p = 0.028) and TMT-B (p = 0.0013) were significantly reduced, but MMSE-DS (p = 0.309) and DST (DSF: p = 0.855, DSB: p = 0.176) were not statistically significant. Depression (p < 0.01) and preventive behavior for dementia (p < 0.0001) of the participants were improved after the IMP. Conclusion: The IMP for dementia prevention may have beneficial effects on cognitive function and depression of elderly. However, a well-designed follow-up study is needed to confirm this conclusion. Keywords: Integrative medicine program, Cognitive function, Public health center, Korean medicine, Health promotion program